Prioritizing knowledge translation in low- and middle-income countries to support pandemic response and preparedness - Yodi Mahendradhata; Anna Kalbarczyk (BMC, 2021)
Abstract The COVID-19 pandemic has created urgent demand around the world for knowledge generation about a novel coronavirus, its transmission, and control, putting academic institutions at the frontline of politics. While many academic institutions are well poised to conduct research, there are well-documented barriers for these institutions, particularly in low- and middle-income countries (LMICs), to further conduct strategic synthesis and dissemination to promote knowledge utilization among policy-makers. These systemic barriers to knowledge translation (KT) pose significant challenges for academic institutions seeking to take advantage of unprecedented policy windows to inform evidence-based decision-making. Global health funding organizations should prioritize the support of academic institutions' activities along the KT pathway, including both knowledge generation and strategic dissemination, to improve knowledge uptake for decision-making to improve health. Institutional capacity-building initiatives for KT have the potential to profoundly impact responses to this and future pandemics.